To find the value of the missing term b, we can compare the given equation (8y^2 - 4y^4) with the simplified expression (40y^4 - 20y^6).
From the given equation, we know that the coefficient of the y^2 term is 8, and the coefficient of the y^4 term is -4.
From the simplified expression, we can see that the coefficient of the y^2 term is 0 (since there is no y^2 term), and the coefficient of the y^4 term is 40.
To find the missing term b, we can set up an equation based on the coefficients:
8 + b = 0 [from the y^2 terms]
-4 + b = 40 [from the y^4 terms]
Solving the first equation:
8 + b = 0
b = -8
Substitute b = -8 into the second equation:
-4 - 8 = 40
-12 = 40
Since -12 does not equal 40, there seems to be an error in the problem.
( b)(8y^2−4y^4)=40y^4−20y^6 find the missing term b
1 answer